Jim Crace's Arcadia: A New Variation On An Old Topic - S. Sultan, Sabbar; Abu Shihab, Ibrahim (Penerbit Universiti Sains Malaysia (USM Press), 2012)
The present paper aims to shed light on an old-new topic in literature and culture in general, i.e., the urban and rural modes of living as reflected in literature. Since times immemorial, this has been an underlying issue, engaging the minds of philosophers, writers, critics, sociologists and artists. As such, this article is devoted to exploring two aspects of this multifarious topic. The first one is a general survey of how writers from different cultures and times have responded to this issue and their priorities. The second presents a reading of Jim Crace's Arcadia (1992) as a contemporary handling of the country-city problematics.